2018
DOI: 10.1002/aelm.201800556
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric Plasticity in Oxide Thin Film Transistors with Tunable Synaptic Functions

Abstract: Emulating key synaptic functions in electronic devices is quite significant in bioinspired applications. Artificial synaptic thin film transistors (TFT) offer a promising solution for efficient synapse simulation. Herein, artificial synapses based on indium–gallium–zinc oxide (IGZO) TFT are fabricated and the photoelectric plasticity is investigated. Versatile synaptic functions including paired‐pulse facilitation, paired‐pulse depression, and short‐term memory to long‐term memory transition are emulated. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(134 citation statements)
references
References 58 publications
(119 reference statements)
5
121
1
1
Order By: Relevance
“…Biological research has generally suggested that the LTM is closely related to the LTP in synapses. Unlike the short‐term changes in synaptic weights in STP, the formation of synaptic weights in LTP can often last for tens of minutes or even years . The transition from STM to LTM, which is considered the basis of biological memory and learning, can be achieved by applying a series of different numbers of pulses.…”
Section: Resultsmentioning
confidence: 99%
“…Biological research has generally suggested that the LTM is closely related to the LTP in synapses. Unlike the short‐term changes in synaptic weights in STP, the formation of synaptic weights in LTP can often last for tens of minutes or even years . The transition from STM to LTM, which is considered the basis of biological memory and learning, can be achieved by applying a series of different numbers of pulses.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, photonic synapse devices have received attention because they have several advantages compared to the electronic synapse devices, such as wide bandwidth, low crosstalk, and low power consumption characteristics 18–28. Therefore, researchers have attempted to mimic synaptic behaviors by utilizing optical stimulation and photonic synapse devices have been realized with various materials such as carbon nanotubes,29,30 oxide semiconductors,18,19,25,31,32 perovskite quantum dots,21,33 2D materials,23,24,27,28,34,35 and hybrid perovskites 20,26,36. These devices have demonstrated synaptic functions, such as short‐term plasticity (STP), paired‐pulse facilitation (PPF), long‐term plasticity (LTP), STP‐to‐LTP transition, and spike‐timing‐dependent plasticity by optical stimulation.…”
Section: Figurementioning
confidence: 99%
“…These devices have demonstrated synaptic functions, such as short‐term plasticity (STP), paired‐pulse facilitation (PPF), long‐term plasticity (LTP), STP‐to‐LTP transition, and spike‐timing‐dependent plasticity by optical stimulation. Among these previously reported photonic synapses, photonic synapses that use the persistent photoconductivity (PPC) phenomenon in oxide semiconductor have advantages such as simple device structure and compatibility with complementary metal–oxide–semiconductor (CMOS) fabrication processes 18,19,31. PPC in photonic synapses based on oxide semiconductors is similar to biological synaptic plasticity in a synapse.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, by modulating the metallic composition ratio in IGZO, some important synaptic behaviors can be accordingly mediated. Recently, Wu et al studied the effect on synaptic behaviors by regulating the element composition ratio of IGZO . They found that compared with the synaptic devices of In L and Ga H , the In H and Ga L devices demonstrate stronger photocurrent generation, which can be explained to higher carrier concentration caused by oxygen vacancies, because In element facilitates the formation of oxygen vacancies, whereas Ga element restrains its formation.…”
Section: Emerging Materials‐based Synaptic Devicesmentioning
confidence: 99%